A moon for Moe & Mo - Zalben, Jane Breskin (Charlesbridge, 2018)
Moses Feldman and Mohammed Hassan both live on Flatbush Avenue, but when they meet at the grocery store they quickly become best friends, sharing a picnic while their families prepare for the holidays of Rosh Hashanah and Ramadan.